Synthesis and Characterisation of Novel Cobalt(li),Copper (II) and Mercury (II) Complexes of Poly Vinyl Urethanised Oxime. - AI-Jeboori, M.J.; Numan, A.T.; Ahmed `, D. J. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The reaction of poly (vinyl alcohol) (PV A) with Urea in (DMSO) resulted in uerthanised oxim, wr,ich reacted with diacetylmonoxime in a (DY.ISOfmethanol) to give anew type (N2) polymeric bidentate imine oxime ligand [HL], The ligand was reacted with MCh (where M= Co, Cu, and Hg). Under reflux in a (DMF/Methanol) mixture with (I:1) ratio to give Complexes of the general formula [M (T.)2]X, (where M= Co,Hg, Cu). All .:ompouncs have been characterized by spectroscopic methods [IR, U.V.-Vis, A tomi<;absorption] microanalysis along with conductivity measurements, from the above:: data the proposed molecular structure for Co,Cu, and Hg is a distorted. Tetrahedml